Activation, Inhibition, or Something Else: An Exploratory Study on Response Priming Using Moving Dots as Primes in Middle-Aged and Old Adults - Christina Bermeitinger; Cathleen Kappes (Journal of Aging Research)
Response priming refers to the finding that a prime stimulus preceding a target stimulus influences the response to the following target stimulus. With young subjects, using moving dot stimuli as primes indicated faster responses to compatible targets (i.e., prime and target are associated with the same response) with short stimulus onset asynchronies (SOAs). In contrast, with longer SOAs, participants responded faster to incompatible targets. In the present study, we extended the evidence by comparing middle-aged (50–65 years) and old (66–87 years) adults. With two different motion types, the result found in young participants was replicated in the middle-aged adults. In contrast, old adults showed large positive compatibility effects with the short SOA but neither activation nor inhibition effects with the longer SOA. We discuss our findings in light of several theoretical accounts (i.e., inhibitory deficit, deautomatization, evaluation window account, attention, rapid decay).